Reliefgenerationen und plio-pleistozäner Klimawandel im Hoggar-Gebirge (Zentrale Sahara) - Büdel, Julius (ERDKUNDE, 1955)
The first goal of this article is to study the genesis of the geomorphology of the Hoggar Massif (central Sahara). This is composed of the interference of endogenous (pluto-tectonic) and exogenous (morphoclimatic) phases. The second goal is more specifically the climatic history of the Hoggar during the Plio-Pleistocene within the framework of the whole Sahara. Apart from my own research, the recent works of Balout, Bordet, and particularly those of Kubiêna will be discussed. This second goal is to explain mainly in the Hoggar Massif and its remote surroundings the existence of three ancient periods of humid climate: Tertiary, Middle Pleistocene and Holocene. The approximate age of these periods will be deduced from their relations with the periods of volcanic eruption, from the comparative study of their successive layers and the degree of conservation of their original forms. The characteristic aspect and the particular duration of each of these periods will be emphasized, because their effect on the geomorphology (morphoclimatic effect) depends on these two factors. The wet Tertiary period (Early Tertiary to Mid-Pliocene) lasted, with interruptions, for many millions of years and resulted in the creation of the extensive and now raised peneplains; layers of red clay testify to their tropical savannah climate with annual alternations of total drought and humidity. The second rainy period corresponds to a cold period of the Middle Pleistocene (perhaps the Alt-Riss, i.e. the most accentuated phase of the Riss). It lasted only a few tens of thousands of years. Its brown paleosol (Braunlehm, brown loam soil) corresponds, according to Kubiëna, to a tropical or subtropical climate that was always humid without significant periods of drought. This period by the construction of the terraces of sandy clay and Parabelhangen generated a deformation also very impressive of the valleys of Hoggar. The reduced rainy period of the Holocene (Neolithic) did not leave geomorphological traces in the central Sahara, but only on its borders. Between these wet periods there are two great periods with a predominantly desert climate: an early Pleistocene period and an Afutre period which extends from the end of the Pleistocene to the present day (except for the small Neolithic interruption). Already in the first period the construction by the erosion of the current dry valleys and by the of the whole current relief of the Hoggar is already for the main part carried out. The second desert period cleared and continued to shape these forms of the relief. The second desert period cleared and continued to shape these landforms. The desert period of the ancient Pleistocene begins with two volcanic phases, that of the ancient basalts and that of the acid lavas, which follow one another without intermediary; it ends with the middle basaltic lavas. The main phase of the Hoggar uplift is situated in this dry period. Correlatively to the second desert period (end of the Pleistocene - Holocene) occurs the more recent basaltic period which lasts until our days.